Acellular Dermal Matrix as a Barrier for Guided Bone Regeneration of Dehiscence Defects Around Dental Implants: A Clinical and Histological Report. Issue 4 (August 2018) - Momen-Heravi, Fatemeh; Peters, Scott M.; Garfinkle, Leonard; Kang, Philip
Abstract : The presence of hard tissue dehiscence and thin periodontal biotype in the esthetic area is a challenge that can jeopardize function and aesthetic outcome of implants. Here, we present a successful simultaneous soft tissue and bone regeneration of dehiscence defects in the maxillary incisor region. The novelty of this case lies in the simultaneous bone regeneration and soft tissue augmentation and the use of acellular dermal matrix as a barrier for regeneration and biotype conversion around dental implants. Reentry surgery 5 months after soft tissue and bone augmentation showed more than 95% new bone formation at the facial surface of implants and histological evidence of new vital bone formation. Biotype conversion from thin (<0.8 mm) to thick (2 mm) was noted in the area.